Patch Solid Lipid Nanoparticles (SLN) Mengandung Ekstrak Bekatul (Oryza Sativa L.) untuk Pengobatan Diabetes Melitus Tipe 2 - maxius gunawan (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2019)
Diabetes mellitus is the increase in blood glucose level by a lack of secretion (insulin resistance) or an absence of pancreatic insulin which is one of the Non-Communicable Diseases (NCDs). 90% of existing cases are of type 2 diabetes mellitus (IDF, 2017). Type 2 diabetes, known as non-dependent-insulin occurs due to tissue resistance to the effects of insulin and the relative deficiency of insulin secretion (WHO, 2016).Type 2 diabetes mellitus is often diagnosed at a younger age and in men with lower body mass index than women. Various risk factors of diabetes are age, physical activity, body mass index (BMI), blood pressure, stress, lifestyle, family history, HDL cholesterol, triglycerides, gestational diabetes, history of glucose abnormalities and other complications. Other risk factors that may play a part are smoking and consuming alcoholic beverages (Isnaini, 2018). According to Riskesdas data in 2013, the prevalence of male smokers was 66%, which is about 10 times higher than women, which is 6.7% (Data and Information Center of the Indonesian Ministry of Health, 2013).Patients with type 2 diabetes mellitus, not only require non-pharmacological therapies such as diet regulation, physical activity, quitting smoking and alcohol, but also require pharmacological therapy that can be carried out by injecting insulin and/or taking oral antidiabetic drugs (Neal, 2012). However, insulin treatment therapy has a problem in patients who are afraid of needles and syringes, besides that, treatment with oral antidiabetic may cause several problems such as weight loss, hypoglycemia, digestive system disorders, etc. The cost of diabetes treatment is quite expensive due to long-term treatment and which may even last a lifetime. The cost needed to provide therapy to patients who have been diagnosed with diabetes worldwide from 2011 to 2030 is 1.7 trillion US$ (WHO, 2016). Considering the high cost of diabetes treatments and the side effects caused by antidiabetic drugs, alternative therapy is needed at a relatively cheaper price, with stronger potency and minimal side effects. This can be done using waste yet it is efficacious for the treatment of diabetes mellitus, an example being rice bran (Sivamaruthi, Kesika, and Chaiyasut, 2018).